Development of Poetry Musicalization Teaching Materials through a Project-Based Learning Model Assisted by Artificial Intelligence Technology - Subandiyono; Ristiani, Iis (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the validation results per procedure for developing poetry musicalization teaching materials using project-based learning models using artificial intelligence technology for grade X of senior high school; 2) the physical profile of the final product of poetry musicalization teaching materials using project-based learning models using artificial intelligence technology for grade X of senior high school; 3) the non-physical profile of the final product of poetry musicalization teaching materials using project-based learning models using artificial intelligence technology for grade X of senior high school. This study employs a research and development method that combines a qualitative and quantitative approach, conducted at SMA Negeri 1 Bojongpicung, utilizing a modified version of the ADDIE procedure. The research respondents consisted of three Indonesian language teachers and nine students per class, serving as the audience. The research population consisted of 62 grade X students, divided into two parallel courses, and the sample was determined to be 54 students based on a statistical formula. The judger team, comprising each expert in poetry musicalization, a literary learning specialist, and a teaching materials expert, was tasked with validating each development procedure through a questionnaire. Interviews were conducted with three Indonesian language teachers and grade X students. The results of the study: 1) 1) the validation results of the teaching material development procedure are rated as mode 4, which is very good; 2) the physical profile of the final product of the teaching material: a) the title is 'The Beauty of Learning Poetry Musicalization in Grade X of Senior High School; b) the final product of the teaching material is typed using Times New Roman on A4 paper. Font size 11 with automatic spacing for 11 pages; c) the final product of the teaching material contains four initial structures and five core structures; 3) the non-physical profile of the final product of the teaching material: a) the validation mode of the feasibility of the final product according to the review team is 'perfect'; b) the teaching material product is effective for use in learning poetry musicalization for grade X of Senior High School